SUGGESTION ACTS EXPRESSED BY THE ELEVENTH GRADE STUDENTS AT SMA NEGERI 2 BANJAR - Sentana, K. W.; Tantra, K. D.; Juniarta, P. A. K. (Jurnal Pendidikan Bahasa Inggris undiksha, 2020)
This study aimed to analyze the social function, text structure, and language features of suggestion acts that expressed by the eleventh-grade students at SMA Negeri 2 Banjar. This research was a descriptive qualitative research and used elicitation technique. The students were given four situations of suggestion acts, such as suggestion of appearance, suggestion of health, suggestion of leisure time, and suggestion of attitude. The results of analysis showed that there were 256 suggestion acts expressed by the eleventh-grade students at SMA Negeri 2 Banjar. Most suggestion acts included recommendation of suggestion acts. There were 192 suggestions included this social function in which the percentage was 75%. Besides, most suggestion acts used text structure of (Subject + Modal Verb + Verb 1). There were 64 suggestion acts used this text structure in which the percentage was 25%. On the other hand, there were 186 suggestion acts used simple present tense in which the percentage was 72%, 109 suggestion acts used specific formula of interrogative form in which the percentage was 42%. Talking about using punctuation of suggestion acts, the most punctuation of suggestion acts that was used by the students was exclamation mark (!), there were 147 suggestion acts used this punctuation in which the percentage was 58%.Keywords: suggestion acts, social function, text structures, language features